Interactive Learning Media Anatomy of 3D Human Skull Using Augmented Reality - Pradityatama, Maharsa; Dharma , I G.B. Budi; Arfian, Nur (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2023)
Anatomy is the study of the structure of the body and the relationship of its parts to one another. Studying human anatomy is mandatory for students of the Faculty of Medicine, especially Medical Education. Based on the results of a preliminary study conducted by the author on students of the Faculty of Medicine, some students stated that they did not understand studying human anatomy only by reading anatomy books such as Sobotta's Atlas of Human Anatomy, Yokochi's Color Atlas of Anatomy, practicum modules. This gave rise to the idea to design an android-based smartphone application using Augmented Reality technology for interactive learning media. Making AR smartphone applications using Unity and Vuforia software with C# programming language. The result of this research is to develop an interactive learning media application of a 3D human skull using augmented reality technology. Interactive learning media provide convenience for students in studying the anatomy of the human skull
Keywords: Anatomy; Skull; Augmented Reality; Smartphone